Spatial Localization of EEG Electrodes in a TOF+CCD Camera System - Chen, Shengyong; He, Yu; Qiu, Huili; Yan, Xi; Zhao, Meng (Frontiers in Neuroinformatics, 2019)
A crucial link of electroencephalograph (EEG) technology is estimating the positions of EEG electrodes. Methods in previous studies, to some degree, can solve data acquisition and operability, but there are still many limitations. Photogrammetry has become an effective method in this field. This study aims to propose a more reliable and efficient method which can acquire 3D information conveniently and locate the source signal accurately in real-time. The main objective is identification and 3D location of EEG electrode positions using a system consisting CCD cameras and Time-of-Flight cameras. To calibrate the camera group accurately, different with the previous camera calibration approaches, a method is introduced in this paper which uses the point cloud directly rather than depth image. Experimental results indicate that the typical distance error of reconstruction in this study is 3.26 mm for real-time applications, which is much better than widely used electromagnetic method in clinical medicine. The accuracy can be further improved to a great extent if using a high resolution camera.